2020
DOI: 10.1111/1440-1681.13273
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of circular RNA circPVT1 restricts cell growth of hepatocellular carcinoma through downregulation of Sirtuin 7 via microRNA‐3666

Abstract: Circular RNAs (circRNAs) have been identified recently as pivotal regulators in the development and progression of cancers, generally by acting as competing endogenous RNAs of microRNAs (miRNAs) to regulate gene expression. The dysregulation of circRNAs in hepatocellular carcinoma (HCC) has attracted much attention, but the precise role of circRNAs in HCC remains largely unknown. In this study, we aimed to investigate the potential role of circular RNA PVT1 (circPVT1), a newly identified cancer‐related circRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 45 publications
(118 reference statements)
1
18
0
Order By: Relevance
“…22 CircPVT1 was reported to be upregulated and could promote HCC cell proliferation by targeting miR-3666 and regulating Sirtuin 7 expression. 23 Consistent with previous reports, we found that circPVT1 level was elevated in HCC tissues and cells, and circPVT1 silence hampered HCC progression in vitro and in vivo. All these results suggested that circPVT1 played an oncogenic role in HCC.…”
Section: Discussionsupporting
confidence: 92%
“…22 CircPVT1 was reported to be upregulated and could promote HCC cell proliferation by targeting miR-3666 and regulating Sirtuin 7 expression. 23 Consistent with previous reports, we found that circPVT1 level was elevated in HCC tissues and cells, and circPVT1 silence hampered HCC progression in vitro and in vivo. All these results suggested that circPVT1 played an oncogenic role in HCC.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, hsa_circRNA_100084/ miR-23a-5p/IGF2 (J. Yang et al, 2020) and circPVT1/miR-3666/ SIRT7 (Li et al, 2020) axes were also discovered in researching HCC progression. There were reasons to believe that the miR-541-3p/ GPX4 axis was accountable for the regulatory role of circIL4R in oncobiology and ferroptosis in HCC.…”
Section: Discussionmentioning
confidence: 91%
“…For instance, hsa_circRNA_00278 regulated breast cancer cellular processes via miR‐328‐3p/COL1A1 axis (Liu, Ye, Ye, Lu, & Han, 2020); hsa_circRNA_0000069 facilitated cervical cancer proliferation and metastasis via miR‐873‐5p/TUSC3 axis (Zhang, Chen, Sun, An, & Xi, 2020); and circNTRK2 served as a tumorigenic role in esophageal squamous cell carcinoma by sponging miR‐140‐3p to up‐regulate NRIP1 (Chen et al, 2020). Similarly, hsa_circRNA_100084/miR‐23a‐5p/IGF2 (J. Yang et al, 2020) and circPVT1/miR‐3666/SIRT7 (Li et al, 2020) axes were also discovered in researching HCC progression. There were reasons to believe that the miR‐541‐3p/GPX4 axis was accountable for the regulatory role of circIL4R in oncobiology and ferroptosis in HCC.…”
Section: Discussionmentioning
confidence: 98%
“… 23 , 32 By downregulating Sirtuin7(SIRT7) via sponging miR‐3666, circPVT1 can promote tumor growth and inhibit cell apoptosis in HCC. 33 Numerous studies have highlighted that circPVT1 can enhance cancer drug resistance and contribute to worse clinical outcome of cancer patients, indicating that targeting circPVT1 may be a promising therapeutic strategy to overcome chemoresistance and improve prognosis of cancer patients. For example, exosomal circPVT1 has been found to induce cisplatin resistance by stimulating YAP1 via sponging miR‐30a‐5p in GC in both vivo and vitro.…”
Section: Discussionmentioning
confidence: 99%